PHARMACOEPIDEMIOLOGY AND ANTIMICROBIAL RESISTANCE DATA FOR BACTERIAL INFECTIONS IN HOSPITALIZED CHILDREN - Pechiareva Sadikarijo, Iskra; Serafimovska, Tijana; Darkovska Serafimovska, Marija; Balkanov, Trajan; Kostova, Elena (Македонско лекарско друштво = Macedonian medical association/De Gruyter, 2019)
Antimicrobial resistance is a global problem that needs an urgent action. The irrational use of antibiotics is widespread and leads to potential usefulness of medicines and negative therapeutic outcome.In April 2016, WHO stated that the problem of antibiotic resistance is a major clinical problem resulting in treatment failures even in a case ofeasy to treat diseases. Resistance to first line medicines results in huge spending on new generation of antibiotics. In some instances resistance to second- and third-line agents is seriously compromising treatment outcome.Seriousness of the situation requires extensive research and constantly monitoring of the spread of bacteria resistance.Another problem regarding bacteria resistance is the lack of new antibiotics reported by the US Center for Control and Prevention of Disease.A systematic literature search of databasesgave us enough information about the use of antibiotics, most often isolated bacteria and resistance to different classes of antibiotics. According to the official data, bacterial resistance is lowest in the countries where guidelines for prescribing and use of antibiotics are consistently implemented, such as Scandinavian countries, The Netherlands, Germany and Great Britain. It is necessary to create a complete database of bacterial resistance and information on whether patients receive medicines appropriate to their clinical conditionin our country.
Keywords: antibiotics; bacterial resistance; multidrug resistance; bacterial pathogens